A Feminist Look at the Death Penalty - Pope, Amy E. (Law and contemporary problems, 2002)
Pope gives an exploration of the need for a feminist perspective on capital punishment. She then begins to determine which feminist methodology is most appropriate to an analysis of the death penalty